A study of competitive advantage that could enhance student enrolment at Institut Teknologi Perwaja / Syaifulyazam Abd Jalil and Nur Diyana Mustapha - Abd Jalil, Syaifulyazam; Mustapha, Nur Diyana (2014)
This paper presents a framework for analyzing the study of competitive advantage that could enhance student enrolment facing by Institut Teknologi Perwaja. This study sought to critically investigate factors that influence student's decision making that could explain Institut Teknologi Perwaja enrolment. The findings identify appropriate factors and indicated that the choice of the institution was made mainly by the students based on brand image or college reputation, financial aids availability, cost or fee of program, employability, and promotion as preferences factors. This study may provide an increase understanding of the selection process and thus assist college in guiding students through the process. The results of this research will be beneficial to Institut Teknologi Perwaja in the strategy development to differentiate themselves in a meaningful way to potential students.